Autoavaliação institucional e processos de identidade no horizonte da cultura avaliativa: estudo de caso em uma Instituição Estadual de Educação Superior - Nardelli, Nelci Janete dos Santos (Universidade do Vale do Rio dos Sinos, 2019)
In Higher Education, attention to the practices focused on institutional evaluation in the last decades has been emphasized as a way of responding to society the reason to exist these institutions and, with that, to establish their identities. The Self-evaluation applied in Higher Education Institutions from the enactment of the law that created the System of Evaluation of Higher Education, Sinaes, is the subject of interest of this research, with the objective of investigating how the engagement in the institutional self-evaluation imposed by this system, can contribute in the processes of the identities of individuals reached by it in a Public University of the State of Paraná. To investigate how the engagement in Unioeste's institutional self-evaluation takes place and whether it can contribute to the identity processes of these individuals is our main objective. In the methodological proposal to develop the research, we used the qualitative approach, with the application of questionnaires to the members of the Unioeste Evaluation Commission - CPA and using the biographical study, which consists in studying the individuals from the description of significant events, through documents or their testimonies, with the application of in-depth interviews with the CPA coordinators and a sectoral committee since 2012. To reach the proposed objectives, we are anchored in the theoretical framework of the comprehensive sociology of Max Weber, which is concerned with extracting the many senses perceived in the same phenomenon through human actions and, as a strategy to reach the answers to the problem that triggered this research, we use the phenomenological approach of Alfred Schutz. The concept of identity is explored from the sociological perspective, having as main references Claude Dubar, J. Ivo Follmann e Stuart Hall. By contrasting the idea of identity processes with the idea of alienation processes, we reinforce the fact that in institutional self-evaluation the engagement of those involved has clear personal and institutional repercussions. The reciprocity of projects aimed at personal and institutional self-knowledge is shown as one of the possibilities of overcoming obstacles that prevent the formation of an evaluation culture that promotes an evaluation model idealized by the individuals reached by this research: a Formative Diagnostic Assessment.

En la Educación Superior la atención sobre las practicas direccionas para la evaluación institucional en las últimas décadas hay sido enfatizada como una forma de responder a la sociedad sobre la razón de existir de esas instituciones y, con eso, firmaren sus identidades. La autoevaluación aplicada en las Instituciones de Educación Superior por medio de la promulgación de la ley que creó el Sistema de Evaluación de la Educación Superior, el Sinaes, es el tema de interés de esta investigación, como el compromiso en la autoevaluación institucional, imposta por esto sistema, puede contribuir en los procesos de identidades de individuos logrados por ella en una Universidad Pública del Estado del Paraná. Investigar como ocurre eso comprometimiento pode contribuir en los procesos de identidad de esos individuos es nuestro objetivo principal. En la propuesta metodológica para desarrollar la investigación, utilizamos el enfoque cualitativo, con aplicación de cuestionarios a los integrantes de la Comissão Própria de Avaliação (Comisión Propia de Evaluación) – CPA de la Unioeste y con utilización del estudio biográfico, que consiste en estudiar los individuos por medio de la descripción de hechos significativos, por medio de los documentos o de sus testimonios, con aplicación de entrevistas en profundidad a los coordinadores de la CPA y de una comissão setorial (comisión sectorial), a partir de 2012. Para lograr los objetivos propuestos, nos basamos en el referencial teórico de la sociología comprensiva de Max Weber, que posee la preocupación centrada en extraer los más diversos sentidos percibidos en un mismo fenómeno, por medio de las acciones humanas. Como estrategia para lograr las respuestas al problema que desencadenó esta investigación, utilizamos el abordaje fenomenológico de Alfred Schutz. El concepto de identidad es explotado por medio de la perspectiva sociológica teniendo como principales referencias Claude Dubar, J. Ivo Follmann y Stuart Hall. Oponiéndose la idea de procesos de identidad a la idea de procesos de alienación reforzamos la contestación de que en la autoevaluación institucional el compromiso de los envueltos presenta claras repercusiones personales e institucionales. La reciprocidad de proyectos direccionadas para el auto conocimiento personal e institucional es presentada como una de las posibilidades de superación de los obstáculos que impiden la formación de una cultura evaluativa que promueve de un modelo de evaluación idealizado por los individuos logrados por esta investigación: una Evaluación Diagnóstica Formativa.
Keywords: Autoavaliação; Autoconhecimento; Educação Superior; Processos de Identidade; Processos de Alienação; Self-evaluation; Self-knowledge; Higher Education; Identity Processes; Alienation Processes; Autoevaluación; Autoconocimiento; Educación Superior; Procesos de Identidad; Procesos de Alienación; ACCNPQ::Ciências Humanas::Sociologia